Fighting Fiction with Fiction—The New Federalism in (a Tobacco Company) Bankruptcy - Jonathan C. Lipson (Washington University Law Quarterly, 2000)
This Article analyzes the new federalism’s impact on Chapter 11 reorganizations. The thesis of this Article is that the fictive nature of the new federalism and the three countervailing doctrines renders them highly unstable in the reorganization context. This instability will inevitably and needlessly distort the negotiations that shape Chapter 11 reorganizations. This Article focuses primarily, but not exclusively, on the effect that the new federalism would have on a tobacco company bankruptcy, because that example impresses these problems into starkest relief. Other Chapter 11 reorganizations could create similar problems, including cases in which the debtor is a gun or lead-paint manufacturer, or a healthcare or educational services provider. This Article offers a solution to this instability: federal bankruptcy courts should, as a constitutional matter, have the power under the Bankruptcy Clause to subordinate or discharge claims held by states, as provided in the Bankruptcy Code. The Bankruptcy Clause, contained in Article I, Section 8, Clause 4 of the United States Constitution, empowers Congress to make “uniform [l]aws on the subject of [b]ankruptcies throughout the United States.” If states’ claims are immune from subordination or discharge in Chapter 11 reorganizations, they will likely receive better treatment than would other, similarly situated creditors. Uniformity in this constitutional context should require uniformity of result. The new federalism should tolerate the subordination and discharge of state claims because Congress carefully tailored the Bankruptcy Code to reflect the needs of the states by giving priority to, and exempting from discharge, a variety of state tax claims.
Keywords: Federal government; Compromise (Law); Tobacco industry – Trials; litigation; etc.; Bankruptcy reorganization; Bankruptcy law